From Tiao Wan (跳丸) to Bakwan (肉丸) and Bakso (肉酥): The Culinary History of Chaoshan Peranakan Cuisine in Java - Budiyanto, Ary (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2026)
The evolution of bakso, especially the variant known as bakwan in Malang, illustrates the complex entanglements of Chinese culinary traditions and Javanese food culture. Historical records, early Chinese agricultural treatises, colonial accounts, and contemporary media provide a foundation for tracing meatball-making techniques and migration routes of Hakka and Teochew communities who helped shape Java’s culinary landscape. Autoethnographic reflections enrich this historical reconstruction by capturing sensory memories, family traditions, and field observations from the 1980s onward. Changes in form, flavor, preparation, and commercialization highlight ongoing negotiations between halal practice, Peranakan heritage, and local taste. The argument frames bakso/bakwan as a cultural node where diaspora history, personal memory, and transregional culinary networks converge.